2016
DOI: 10.1080/1369183x.2016.1238758
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between objective and subjective ethno-cultural diversity in predicting intergroup relations

Abstract: This nation-wide probability sample survey study among Finnish majority group members (N = 335) focused on the interactive effects of objective and subjective ethno-cultural diversity on three indicators of intergroup relations: outgroup attitudes, perceived group and personal discrimination, and outgroup trust. Complementing previous research that has mostly examined a linear relationship between cultural diversity and intergroup relations, special attention was given to moderate diversity contexts, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We unfortunately lack data on interethnic friendships and acquaintances for the participants in the trust game to take into account such variation in intergroup contact. Second, some scholars have pointed out that the effect of ethnic diversity on intergroup relations may not be linear but instead depend on a number of factors, such as the perceived diversity level [ 66 ]. For example, in Finland, research has found that majority group members in contexts with moderate levels of objective diversity but subjective perceptions of high levels of diversity will report greater negative outgroup trust than Finnish majority members in low- or high-diversity context [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We unfortunately lack data on interethnic friendships and acquaintances for the participants in the trust game to take into account such variation in intergroup contact. Second, some scholars have pointed out that the effect of ethnic diversity on intergroup relations may not be linear but instead depend on a number of factors, such as the perceived diversity level [ 66 ]. For example, in Finland, research has found that majority group members in contexts with moderate levels of objective diversity but subjective perceptions of high levels of diversity will report greater negative outgroup trust than Finnish majority members in low- or high-diversity context [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…Second, some scholars have pointed out that the effect of ethnic diversity on intergroup relations may not be linear but instead depend on a number of factors, such as the perceived diversity level [ 66 ]. For example, in Finland, research has found that majority group members in contexts with moderate levels of objective diversity but subjective perceptions of high levels of diversity will report greater negative outgroup trust than Finnish majority members in low- or high-diversity context [ 66 ]. We acknowledge that subjective perceptions are important but, unfortunately, such measures are also unavailable in the GSOEP data and we therefore rely on a measure of objective ethnic diversity as our contextual measure.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, such discrepancy is visible regardless of the status of the group within the society, and there is a small but growing body of research showing that personal-group discrepancy in discrimination applies to both underprivileged and privileged groups (Postmes et al, 1999). Similarly, Celikkol et al (2017) found that Finnish majority group members in Finland perceived higher levels of group discrimination than personal discrimination.…”
Section: Personal and Group Evaluations Of Perceived Discrimination And Economic Insecuritymentioning
confidence: 99%
“…Another concern among national majorities related to immigration is increased feelings of being a target of the minority’s prejudice and subsequent insecurity ( Kluegel and Bobo, 2001 ; Norton and Sommers, 2011 ). There is research showing that also advantaged national majority groups report ethnic discrimination and that it is associated with their negative attitudes toward immigrants and immigration (e.g., Celikkol et al, 2017 ). According to Grigoryev et al (2020) , particularly those majority group members who have a negative outlook on the social world by perceiving it as dangerous and competitive (cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation